Clinical value of next‐generation sequencing compared to cytogenetics in patients with suspected myelodysplastic syndrome. (25th June 2020) - Kawata, Eri; Lazo‐Langner, Alejandro; Xenocostas, Anargyros; Hsia, Cyrus C.; Howson‐Jan, Kang; Deotare, Uday; Saini, Lalit; Yang, Ping; Broadbent, Robert; Levy, Michael; Howlett, Christopher; Stuart, Alan; et al.
Summary: Next‐generation sequencing (NGS) increasingly influences diagnosis, prognosis and management of myelodysplastic syndrome (MDS). In addition to marrow morphology and flow cytometry, our institution performs cytogenetics (CG) and NGS‐based testing routinely in patients with suspected MDS. We evaluated the relative value of NGS in the assessment of patients with suspected MDS. We initially compared the diagnostic and prognostic information derived from CG and NGS in 134 patients. NGS enhanced the diagnostic yield compared to CG for clonal myeloid disorders (sensitivity 77% vs. 42·2%; specificity 90·2% vs. 78%; positive predictive value 92·8% vs. 76%; and negative predictive value 70·8% vs. 45·5%). The identification of poor prognosis mutations by NGS altered risk category in 27/39 (69·2%) patients with MDS with good/intermediate risk CG. Subsequently, we prospectively evaluated 70 patients with suspected MDS using an 'NGS‐first approach' with CG restricted to samples with morphological abnormalities. We rarely identified mutations or CG abnormalities in patients without dysplastic features. NGS has a superior diagnostic performance compared to CG in patients with suspected MDS. We estimate that by using an 'NGS‐first approach' we could reduce karyotyping by approximately 30%.